2012
DOI: 10.2967/jnumed.111.100214
|View full text |Cite
|
Sign up to set email alerts
|

Bringing Physiology into PET of the Liver

Abstract: Several physiologic features make interpretation of PET studies of liver physiology an exciting challenge. As with other organs, hepatic tracer kinetics using PET is quantified by dynamic recording of the liver after the administration of a radioactive tracer, with measurements of time–activity curves in the blood supply. However, the liver receives blood from both the portal vein and the hepatic artery, with the peak of the portal vein time–activity curve being delayed and dispersed compared with that of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 42 publications
2
38
0
Order By: Relevance
“…Conventionally it is either obtained by invasive arterial blood sampling or noninvasively derived from the left ventricle or aortic regions in dynamic PET images (3941). In the liver, both the hepatic artery and portal vein provide blood supply to the hepatic tissue (22). The portal vein input is not the same as the hepatic artery input and is difficult to obtain in human subjects (22).…”
Section: Introductionmentioning
confidence: 99%
“…Conventionally it is either obtained by invasive arterial blood sampling or noninvasively derived from the left ventricle or aortic regions in dynamic PET images (3941). In the liver, both the hepatic artery and portal vein provide blood supply to the hepatic tissue (22). The portal vein input is not the same as the hepatic artery input and is difficult to obtain in human subjects (22).…”
Section: Introductionmentioning
confidence: 99%
“…A potential decrease in FDG concentration in the hepatocytes compared to CRLM, due to high glucose-6-phosphatse activity, was therefore minimal and the effect on possibly increased sensitivity of rgPET/CT negligible [22,23]. Dirisamer et al found that a delayed PET-scan could improve sensitivity for liver metastases [24].…”
Section: Discussionmentioning
confidence: 97%
“…Imaging techniques include PET, SPECT, and MRI. Because several recent reviews have documented the role of PET (Keiding, 2012;Kusuhara, 2013;Yoshida et al, 2013) and SPECT (de Graaf et al, 2010) in assessing the severity of human liver diseases, we focus on how MRI assesses focal lesions, diffuse liver diseases, and bile duct injury.…”
Section: Transport Mechanisms Of Organic Anion Transportersmentioning
confidence: 99%
“…Thus, magnetic resonance imaging (MRI), positron emission tomography (PET), single photon emission computed tomography (SPECT), and fluorescence imaging help clinicians to manage human liver diseases (Bae et al, 2012;Keiding, 2012;Stieger et al, 2012;Van Beers et al, 2012;Hoekstra et al, 2013;Kusuhara, 2013). Following a brief overview of the transport through OATPs and MRPs, this review highlights how MRI with hepatobiliary contrast agents is important to diagnose liver diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation